KEANEKARAGARAM HAYATI DI RAWA DANAU PANGGANG KABUPATEN HULU SUNGAI UTARA - Erma Agusliani; Deddy Dharmaji (Universitas Lambung Mangkurat, 2017)
The Danau Panggang swamp is one of the potential swamp waters as a producer of swamp fish in South Kalimantan. The objective of the research is to identify the potential of fish resources, macrophytes, and plankton in Danau Panggang swamp. The results showed that fish caught in Swamp Danau Panggang waters are 22 species. The macrophytic water plants found in the Danau Panggang Swamp Waters are 11 species. The results of phytoplankton and zooplankton analyzes are found for phytoplankton dominated by Chrysophyta phyla, while zooplankton is dominated by the Protozoa order. The condition of the Danau Panggang swamp water quality is still relatively in accordance with the Baku Mutu Air Kelas 2 PP No 82 Tahun 2001